EFEKTIVITAS APLIKASI KANJI MEMORY HINT 2 TERHADAP KEMAMPUAN KANJI DASAR MAHASISWA PENDIDIKAN BAHASA JEPANG, UNIVERSITAS RIAU - Muhammad Amarullah; Nana Rahayu; Adisthi Martha Yohani (Universitas Pendidikan Ganesha, 2024)
This study was conducted to determine the effectiveness of the Kanji Memory Hint 2 application on basic kanji abilities in students of the class of 2022 of the Japanese Language Education Study Program, Riau University. The sample used in this study amounted to 37 people who were students of the class of 2022 of the Japanese Language Education Study Program, Riau University. This research is experimental research with a one group pre-test post-test design. Data were collected using tests in the implementation of pre-test and post-test. From the pre-test and post-test data were then analyzed using paired sample t-test. It was found that the paired sample t-test result of 0.000 so that it can be interpreted that the Memory Hint 2 Kanji application is effective for the kanji ability of students of the class of 2022 of the Japanese Language Education Study Program, Riau University. It can be concluded that the Memory Hint 2 Kanji is able to improve student’s ability to memorize the meanings of kanji, read and use kanji Keywords : Effectiveness, app, Kanji Memory Hint 2, kanji skills. Abstrak Tujuan dilakukannya penelitian ini adalah untuk mengetahui efektivitas dari aplikasi Kanji Memory Hint 2 terhadap kemampuan kanji tingkat dasar pada mahasiswa angkatan 2022 Program Studi Pendidikan Bahasa Jepang, Universitas Riau. Sampel yang digunakan pada penelitian ini berjumlah 37 orang yang merupakan mahasiswa angkatan 2022 Program Studi Pendidikan Bahasa Jepang, Universitas Riau. Penelitian ini merupakan penelitian eksperimen dengan desain one group pre-test post-test. Data dikumpulkan menggunakan tes pada pelaksanaan pre-test dan post-test. dari data pre-test dan post-test tersebut kemudian dianalisis menggunakan uji paired sample t-test. Didapati hasil uji paired sample t-test sebesar 0.000 sehingga dapat ditafsirkan bahwa aplikasi Kanji Memory Hint 2 efektif terhadap kemampuan kanji mahasiswa angkatan 2022 Program Studi Pendidikan Bahasa Jepang, Universitas Riau. Dapat disimpulkan bahwa aplikasi Kanji Memory Hint 2 mampu untuk meningkatkan kemampuan mahasiswa dalam menghafal makna, membaca dan menggunakan kanji.